2008
DOI: 10.1021/jf8018722
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Dioscorea batatas Induce Tumor Necrosis Factor-α Secretion via Toll-like Receptor 4-Mediated Protein Kinase Signaling Pathways

Abstract: The bioactive polysaccharides (named ZPF1) from yam (Dioscorea batatas) were chemically determined, suggesting repeating β-1,4-mannan as mainly having a feature of acetylation on C2−OH and C3−OH, around 28%. The ZPF1 participated in the stimulation of murine wild-type macrophages predominantly in tumor necrosis factor-α (TNFα). Toll-like receptor 4 is proved to be one of the cellular receptors in ZPF1-mediated TNFα secretion. Reactive oxygen species transmission and PI3-kinase are found necessary for regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…5 extract, designated as DsII-TN5, effectively enhanced the DC-mediated activation of T-cell proliferation and suppressed the growth of melanoma tumor cells in vivo (Chang et al, 2013). Mechanistically, other studies showed that immunological activities of specific polysaccharides and/or glycoproteins in Dioscorea tubers were in part due to their TLR4-signaling pathway-mediated immunomodulatory and cytokine-regulation activities (Fu et al, 2006; Liu et al, 2008). Moreover, our previous study further showed that Dioscorea phytoextracts can enhance the proliferation of murine splenocytes ex vivo and promote regeneration of specific myeloid-derived progenitor cells in chemotherapy-damaged bone marrow tissues (Su et al, 2011).…”
Section: Regulation Of Immune Cells In the Tumor Microenvironment By mentioning
confidence: 99%
“…5 extract, designated as DsII-TN5, effectively enhanced the DC-mediated activation of T-cell proliferation and suppressed the growth of melanoma tumor cells in vivo (Chang et al, 2013). Mechanistically, other studies showed that immunological activities of specific polysaccharides and/or glycoproteins in Dioscorea tubers were in part due to their TLR4-signaling pathway-mediated immunomodulatory and cytokine-regulation activities (Fu et al, 2006; Liu et al, 2008). Moreover, our previous study further showed that Dioscorea phytoextracts can enhance the proliferation of murine splenocytes ex vivo and promote regeneration of specific myeloid-derived progenitor cells in chemotherapy-damaged bone marrow tissues (Su et al, 2011).…”
Section: Regulation Of Immune Cells In the Tumor Microenvironment By mentioning
confidence: 99%
“…A specific polysaccharide fraction from Reishi stimulated immune cell activation including dendritic cell maturation and cytokine expression and displayed potent adjuvant activity in mice [153, 154]. Polysaccharides from Dioscorea batatas were found to induce TNF- α secretion via Toll-like receptor 4-mediated protein kinase signaling pathways [155]. A number of phytochemicals have also been demonstrated to effectively enhance the anti-tumor potency of gene-based cancer vaccines.…”
Section: Other Anticancer Applications Of Specific Herbal Medicinesmentioning
confidence: 99%
“…For example, polysaccharides ASP and G1-4A , which were isolated from Acanthopanax senticosus and Tinospora cordifolia , respectively, activated macrophages and B cells by interacting with TLR4 [54,55]. TLR4 was also found to be one of the cellular receptors mediating TNF secretion induced by ZPF1 , polysaccharide isolated from Dioscorea batatas [56]. Likewise, polysaccharide CWSP from Chlorella pyrenoidosa induced cytokine secretion in macrophages via TLR4-mediated signaling pathways [57].…”
Section: Discussionmentioning
confidence: 99%